Multiproxy reconstruction of past methane emissions at Storfjordrenna Pingos site (South of Svalbard) during the last deglaciation - Paavilainen, Anne (UiT Norges arktiske universitet, 2023)
The main ambition of this thesis was to study the relationship between isotopic signature of fossil foraminifera and past methane emission at Storfjordrenna Pingos site (South of Svalbard) during the last deglaciation in context of past climatic changes. Two gravity cores, the core 1070 from the flank of the presently inactive gas hydrate pingo 5 (GHP5) and the core 1069 from the top of the GHP5, were investigated in detail. Combined benthic and planktic δ13C records, visual investigations (SEM-EDS) of the foraminiferal tests and the solid phase composition of the sediment (XRF) revealed interesting and complex methane seepage history at the presently inactive GHP5. Several paleo seepage events were found from deglaciation and Holocene deposits.